Brane-bulk neutrino oscillations - Lukas, A; Ramond, P; Romanino, A; Ross, G (2001)
A plausible explanation for the existence of additional light sterile neutrinos is that they correspond to modulini, fermionic partners of moduli, which propagate in new large dimensions. We discuss the phenomenological implications of such states and show that solar neutrino oscillation is well described by small angle MSW oscillation to the tower of Kaluza Klein states associated with the modulini. We also consider how all oscillation phenomena can be explained in a model including bulk neutrino states.